Pain Managment of Multiple Rib Fractures on the Basis of Early Reduction and Fixation in Patients without Intensive Care Unit. - ağababaoğlu, ismail (Acta Medica, 2019)
Objective: Blunt thoracic traumas are often complicated with rib fractures. The decision-making process of the treatment approaches not clear for clinicians. So, we aim to investigate the effect of surgical intervention on pain managment of patients as treatment indication. Methods: Cases with 3 or more rib fractures were evaluated in our study. 84 patients underwent open reduction from 2014 to 2018 and 127 patients were treated conservatively from 2014 to 2018 included in the study. Surgery was performed for all cases in first 24-36 hours and no patient needed intensive care. The results of hospitalization time, pneumonia, rates, thoracic deformity rates on 6.month thorax computerized tomography, intercostal blockage requirement, postoperative 6.month quality of life questionnaire for pain and clinical outputs of two groups were retrospectively analyzed. Results: The average hospitalization was found that it was significantly different in favor of the surgical group (z = 6.674; p <0.001). Thoracic deformity rates, intercostal blockage requirement was found to be different between the surgery and non-surgery groups (χ2=7.149;p<0.001), (χ2=22.462;p<0.001). Pain and quality of life scores had also significant difference in favor of the surgical group, respectively (z = 9.270; p <0.001) and (z = 8.796; p <0.001). Additionally there was statistical difference in pneumonia rates (p= 0.020). We did not reach a statistically significant result between the early and late groups in pain 1 and pain 2 results (p1: 0.727, p2: 0.069). Conclusions: There is no consensus on rib fractures. The results of our study suggest that open rib reduction and fixation can be better treatment option than conservative approach in terms of pneumonia rates, hospitalization time, thoracic deformity rates and pain management.